PERLINDUNGAN ANAK SEBAGAI KORBAN INCEST DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Khairul, Muhammad; Firdaus, Emilda; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
One form of the type of sexual crimes affecting children as victims is that intercourse with someone who still have blood relations (incest) are usually largely prosecuted are children. There have been many cases of incest that happens, but very limited (few) are revealed, because this case is regarded as a family disgrace. Known to the general public if the family concerned will cause the embarrassment in social life society. Therefore incest is very little that is to report to the authorities.The research objective of this thesis, namely; First, to determine the legal protection of children as victims of incest in the laws and regulations in Indonesia. Second, to determine the factors behind the ineffectiveness of the legal protection of children as victims of incest. This type of research is the author of normative legal research or known by the term legal research.From the research, there are two fundamental problems that can be inferred. First, the legislation was not found understanding of the biological child victims. So does this impact the equation of handling specific to children as victims either from his own family (biological children) with children outside the family (children of others), which is clearly different from the psychological impact of the crime of rape victims biological children (incest). Second, the factors underlying the ineffectiveness of the legal protection of children as victims of incest is due among other things that the child victims of incest tend to be not open, family considers the incident is a disgrace, environmental and social factors which have not the law to accommodate the interests of victims of incest in maximum. Suggestions Author, First, the President and Parliament as state officials should undertake legal reforms, especially those governing sexual crimes in the family (incest), so that law enforcement and the legal protection do more specialized and specific in handling cases of incest are clearly distinct from the crime sexual usually. Secondly, The high crime rate amongst the people especially sexual violence requires us to perform law enforcement more leverage to perform various prevention efforts, namely the active dissemination of the impact of sexual violence to the perpetrator and the victim to similar crimes are not repeated. And is expected to law enforcement officials, especially judges to be more serious in imposing legal sanctions on perpetrators of incest.Keywords: Incest - biological children - Victims - Relationship Tribe